2017
DOI: 10.17741/bgsf/89.2.001
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution LiDAR mapping of glacial landforms and ice stream lobes in Finland

Abstract: Newly available high resolution airborne LiDAR (Light Detection And Ranging) technology is generating unprecedented next-generation imagery of Earth surface features. LiDAR datasets are being employed by the Geological Survey of Finland (GTK) as part of a new national geological initiative (Glacier Dynamic database: GDdatabase) to rapidly and cost-effectively map glacial landforms and sediments left by the last (Late Weichselian) Fennoscandian Ice Sheet (FIS). There is a high demand for such data in hydrogeolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
(53 reference statements)
0
30
0
Order By: Relevance
“…Figure 2 shows the interpreted ice flow directions over the LiDAR-based digital elevation model. About 9000 different types of lineations were mapped and classified into one of five categories based on the GTK's Glacier Dynamic database (see Putkinen et al, 2017 in this volume). These were: drumlins, megascale glacial lineations (MSGLs), rock drumlins, pre-crags and flutings.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the interpreted ice flow directions over the LiDAR-based digital elevation model. About 9000 different types of lineations were mapped and classified into one of five categories based on the GTK's Glacier Dynamic database (see Putkinen et al, 2017 in this volume). These were: drumlins, megascale glacial lineations (MSGLs), rock drumlins, pre-crags and flutings.…”
Section: Methodsmentioning
confidence: 99%
“…A wealth of work at the margins of modern ice sheets in Antarctica, Greenland, and Spitsbergen has shown that MSGLs are the geomorphic fingerprint of dynamic fast-flowing ice streams (King et al 2009;Stokes 2011;Livingstone et al 2012;Dowdeswell et al 2016;Fernandez et al 2018). They are now widely identified on the beds of Pleistocene and pre-Pleistocene ice sheets, indicating that they too were similarly structured (Le Heron 2017; Putkinen et al 2017;Stokes et al 2016;Margold et al 2014Margold et al , 2015Margold et al , 2018Stokes 2018). Today, almost 200 ice streams are currently recognized in the last Cordilleran and Laurentide ice sheets (Clark 1993;Patterson 1997;Dyke 2008;Kleman 2005, 2007;Evans et al 2006Evans et al , 2008Evans et al , 2014Ross et al 2006Ross et al , 2009Ross et al , 2011Ó Cofaigh et al 2010aÓ Cofaigh et al , 2013MacLean et al 2010MacLean et al , 2015MacLean et al , 2017Occhietti et al 2011;Paulen et al 2017;McMartin 2017;McMartin et al 2018;Veillette et al 2017;Shaw and Longva 2017;Margold et al 2018;Eyles et al 2018a).…”
Section: Shane Sookhan Nicholas Eyles and Lina Arbelaez-morenomentioning
confidence: 99%
“…The glacial lineations studied were mapped manually using ESRI's (Environmental Systems Research Institute) ArcMap 10.3 software and the GTK's database classification for landforms (Putkinen et al, 2017, Supplementary file 2; this volume). The lineation data in ArcMap-format is saved in the GTK's personal geodatabase.…”
Section: Landform Mappingmentioning
confidence: 99%